ANALISIS KANDUNGAN SERAT DAN UJI HEDONIK PADA PRODUK SNACK BAR TEPUNG BERAS MERAH (Oryza Nivara L) DAN KACANG HIJAU (Phaseolus Radiatus L) - Nathasya YP, Nanda; Hermanto, Restu Amalia; Ulfah, Ardhika (Sekolah Tinggi Ilmu Kesehatan Holistik, 2019)
Background: The level of fiber consumption of Indonesian people is seen from the level of consumption of vegetables and fruit as a source of fiber still low.Snack bar is a snack made from cereals and nuts can be an alternative source of fiber. Objective: To determine the effect of ratio of red rice flour and mung beans to the Hedonic test, fiber content, the best formulation in making snack bars and determine the contribution of fiber contained in snack bars to Recommended Dietary Allowance (RDA) Method: This research uses quantitative method using Rancangan Acak Lengkap (RAL) with one variable which is the comparison of the ratio of grain rice and mung bean in the Snack Bar production process within three repetition processes. This Research consist of three steps; the production of Snack Bar, The analysis of fiber content and Hedonic Test using 60 panelist from general age range. The statistical analysis conducted by using the One Way Anova and Cruscal Wallis test. Results: The result of the research shows that there is no significant difference of fiber content of Snack Bar (p>0.05) and p value 0.055. The result of Hedonic Test towards the color parameter is p value 0.699, Scent parameter is p value 0.913, taste parameter is p value 0.762 and texture parameter is p value 0.708 or (p<0,05). In conclusion, based on the Snack Bar’s Hedonic Test there are no major effect towards color, scent, taste and texture parameter in each formulation. Conclusion: There are no major effect or correlation between the ratio of rice grain and green peas towards the fiber content and Hedonic Test of snack Bar. Snack Bar 60g : 40g is considered as the best formulation although it has not fulfill the fiber adequacy level per day.